Is Chinese Tallowtree, Triadica sebifera, an Appropriate Target for Biological Control in the United States?. (June 2014) - Wheeler, Gregory S.; Ding, Jianqing
Abstract: Biological control is one of the most common approaches used to manage invasive weeds of wetlands and other natural areas. Before candidate agents can be released, research is conducted to support biological control, which can be protracted and expensive, leading to a scientific and potentially lengthy regulatory review. To increase biological control safety, efficacy, and transparency, we suggest that during the early phases of a weed project, the feasibility of the invasive plant as a target should be studied explicitly. Our purpose here is to summarize information of an important invasive weed that can serve to judge whether the project is appropriate. Chinese tallowtree, Triadica sebifera, is one of the worst invasive species invading coastal wetlands and other riparian areas of the southeastern United States. Current management practices have not controlled the spread of this weed into these sensitive habitats. Initial surveys in the plant's native Chinese range for potential biological control agents have recovered several herbivore species that could be developed. These potential agents include defoliators, root and foliage feeders, and gall formers, whose biology, apparent host specificity, and impacts on plant fitness suggest that biological control offers great promise against Chinese tallowtree. When conducted during the initial phase of a project, this type of feasibility study can address potential conflicts of interest and risks, ultimately producing projects that are more effective and safer for biological control.